Assessment of the fish diet of the Caspian seal (Pusa caspica Gmelin, 1788) during haul out periods on island sites: results, challenges, and perspectives - Baimukanov, Mirgaliy; Shagilbayev, Anuar; Iskakov, Akzhan; Baimukanova, Assel (Frontiers in Marine Science, 2025)
The Caspian seal (Pusa caspica), an endemic and endangered obligate piscivore of the Caspian Sea, faces threats to its existence, notably from the reduction of its food resources. Pollution, sea regression, overfishing, and the introduction of non-native species have negatively impacted the seal’s food base. The seals annually gather in haul‐outs during the spring and autumn, a span of approximately 4–6 months. The diet of seals during these critically important periods of life is poorly understood. The fish diet of the P. caspica was assessed by analyzing fish otoliths found in fecal samples collected at haul-out sites in the Northern and Middle Caspian Sea from 2015 to 2022. A total of 8,630 fish otoliths and their fragments were recovered from the fecal samples. The taxonomic status was determined for 94% of the otoliths. Their taxonomic identification was carried out using a reference collection of otoliths obtained directly from 323 individuals representing various fish species. Brief descriptions were made of otoliths from 14 fish species representing Clupeidae, Gobiidae, Cyprinidae, Mugilidae, and Atherinidae. For Cyprinidae, the asteriscus and lapillus were described; for all others, the sagitta. The dietary diversity of seals during their haul-out periods was determined at the species level for golden grey mullet (Chelon auratus) and big-scale sand smelt (Atherina boyeri); at the genus level for shad (Alosa) and tyulka (Clupea); and at the family level for gobies (Gobiidae) and cyprinids (Cyprinidae). Gobies dominate the diet (79.34%), followed by big-scale sand smelt at 15.99%. According to Margalef’s richness index, the diet was more diverse in the deepwater Middle Caspian region. In the future, investigating the seals’ diet in relation to fish distribution at haul-out sites will significantly contribute to understanding their adaptation to rapidly changing conditions and the development of conservation measures for key habitats of this endangered marine mammal of the Caspian Sea. Establishing a comprehensive database of fish otoliths from various regions of the sea is essential for investigating their morphological polymorphism and for applying DNA barcoding in the future to achieve a more accurate assessment of the species composition in the diet of the Caspian seal.